Annotation: behavioural phenotypes: a window onto the biology of behaviour. - Flint, J (1996)
Characteristic behavioural patterns (including cognitive processes and social interactions) have been reported in a number of syndromes arising from genetic or chromosomal abnormalities, suggesting that molecular analysis of the underlying defect could reveal the biological basis of the behavioural phenotype. Because of the rarity of many of the syndromes, and the complexity of their genetic basis, there are great difficulties in establishing the validity of the association between syndrome and behavioural phenotype. Nevertheless, evidence from animal studies with relevance to human behavioural phenotypes shows that the pathway from genotype to phenotype may be accessible by careful delineation of behavioural phenotypes.